DESAIN VIDEO PEMBELAJARAN CERITA RAKYAT BERBASIS TEACHING AT THE RIGHT LEVEL TERHADAP KEMAMPUAN PENALARAN MATEMATIS SISWA SMA PADA MATERI MATRIKS - Salsabila Qurratu'ain; Utin Desy Susiaty; Hartono (STKIP Subang, 2026)
This study aimed to develop folklore-based learning videos using the Teaching at the Right Level (TaRL) approach to enhance senior high school students mathematical reasoning abilities on matrix material. The research employed a Research and Development (R&D) method using the ADDIE development model, which consists of Analysis, Design, Development, Implementation, and Evaluation stages. Data were collected through validation sheets, teacher and student response questionnaires, and posttest instruments. The subjects of this study were Grade XI students of SMA Negeri 1 Sungai Ambawang. The results indicated that the developed learning video was categorized as very valid, with an average validation score of 87.5% based on assessments by media and material experts. The learning video was also categorized as very practical, obtaining an average practicality score of 93% from teacher and student responses. Furthermore, the effectiveness test showed that 77.7% of students achieved the minimum learning mastery criteria, indicating that the learning video was effective. Therefore, the folklore-based learning video integrated with the Teaching at the Right Level (TaRL) approach is feasible and effective for use in mathematics learning, particularly on matrix material.